2023
DOI: 10.3389/fnut.2023.1082217
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ramadan intermittent fasting on anthropometric measurements and body composition: Evidence from LORANS study and a meta-analysis

Abstract: BackgroundAlthough the effect of Ramadan intermittent fasting (RIF) on anthropometry and body composition has been questioned, none of the previous studies tried to explain the reported changes in these parameters. Also, systematic reviews that investigated the topic were limited to healthy individuals or a specific disease group.MethodsThe London Ramadan Study (LORANS) is an observational study on health effects of RIF. We measured weight, waist circumference (WC), hip circumference (HC), body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 83 publications
3
5
0
3
Order By: Relevance
“…Although both intervention groups showed significant reductions in waist and hip circumference after 6 months, greater mean differences were observed among participants in the IFHP group. Previous studies reported a similar significant reduction in waist and hip circumference after IF [ 34 , 41 , 42 ]. The London Ramadan Study is an observational study conducted during Ramadan to explore the health consequences of Ramadan IF.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although both intervention groups showed significant reductions in waist and hip circumference after 6 months, greater mean differences were observed among participants in the IFHP group. Previous studies reported a similar significant reduction in waist and hip circumference after IF [ 34 , 41 , 42 ]. The London Ramadan Study is an observational study conducted during Ramadan to explore the health consequences of Ramadan IF.…”
Section: Discussionsupporting
confidence: 69%
“…The London Ramadan Study is an observational study conducted during Ramadan to explore the health consequences of Ramadan IF. Besides other findings, this study showed a significant decrease in waist (mean difference −1.93 cm; P <.01) and hip circumference measurements (mean difference −2.86 cm; P <.01) [ 41 ]. In the IFHP group, we observed a significant decrease in both parameters during the unsupervised phase of the intervention (from month 3 to month 6).…”
Section: Discussionsupporting
confidence: 60%
“…Ramazan orucunun süresi, mevsime ve coğrafi konuma bağlı olarak değişmekte (1,2) olup bu çalışmanın gerçekleştirildiği tarihte Ramazan ayı Nisan ayına denk gelmiş ve yaklaşık olarak günün 14.5 saati oruç tutulmuştur. Ramazan döneminde uyku süresi, fiziksel aktivite, vücut bileşimi, besin tüketimi ve hidrasyon durumu etkilenebilmektedir (29)(30)(31)(32)(33)(34). Yemek saatindeki değişiklikler de uyku düzenini etkileyebilmektedir (35).…”
Section: Discussionunclassified
“…Literatür incelendiğinde Ramazan dönemindeki antropometrik ölçümler ve vücut bileşimine yönelik sonuçlar farklılık göstermektedir ve bu ilişki arasındaki mekanizma net değildir (30)(31)(32). Madkour ve ark.…”
Section: Discussionunclassified
“…Supplemental Table 1 compares the study sample’s demographics ( n = 72) to those of people not attending the second visit ( n = 68); the 2 groups were similar except for age. In addition to blood samples, we collected socioeconomic and lifestyle data using online questionnaires and measured blood pressure using an automatic blood pressure monitor and body composition using a bioelectrical impedance analyzer at each visit, more details reported elsewhere [ 10 , 11 ].
FIGURE 1 Significant changes in individual metabolites (normalized between 0 and 1) among LORANS participants after Ramadan fasting.
…”
Section: Methodsmentioning
confidence: 99%